2018
DOI: 10.1038/s41559-018-0548-9
|View full text |Cite
|
Sign up to set email alerts
|

The ash dieback invasion of Europe was founded by two genetically divergent individuals

Abstract: Accelerating international trade and climate change make pathogen spread an increasing concern. Hymenoscyphus fraxineus, the causal agent of ash dieback, is a fungal pathogen that has been moving across continents and hosts from Asian to European ash. Most European common ash trees (Fraxinus excelsior) are highly susceptible to H. fraxineus, although a minority (~5%) have partial resistance to dieback. Here, we assemble and annotate a H. fraxineus draft genome which approaches chromosome scale. Pathogen geneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 57 publications
(73 reference statements)
6
100
0
Order By: Relevance
“…This bi‐allelic pattern has already been found and described in more detailed population genetic studies of H. fraxineus (Burokiene et al, ; Gross, Hosoya, & Queloz, ; Schoebel, Botella, Lygis, & Rigling, ). It points to a strong founder effect due to the limited initial number of two‐parent genotypes upon the introduction of H. fraxineus in Europe (McMullan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This bi‐allelic pattern has already been found and described in more detailed population genetic studies of H. fraxineus (Burokiene et al, ; Gross, Hosoya, & Queloz, ; Schoebel, Botella, Lygis, & Rigling, ). It points to a strong founder effect due to the limited initial number of two‐parent genotypes upon the introduction of H. fraxineus in Europe (McMullan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Junker, Vries, Eickhorst, and Schulz () demonstrated that each investigated H. fraxineus isolate has its own exoenzyme profile. The European population of H. fraxineus went through a genetical bottleneck and virulence of co‐infecting pathogens can increase with increasing genetic relatedness (Buckling & Brockhurst, ; McMullan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other hemibiotrophs, including P. infestans , the H. fraxineus genome encodes an impressive array of plant cell wall‐degrading enzymes (Stenlid et al ., ; McMullan et al ., ). Apart from the highly localized degradation of primary and secondary cell walls at penetration sites, there was very little sign of cell wall‐degrading enzyme activity during the stages of biotrophic and necrotrophic invasion examined, despite the formation of large lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous genes encoding potential virulence factors have been identified. Both Stenlid et al (2017) and McMullan et al (2018) pointed out the high frequency of cell wall-degrading hydrolases and cytochrome P450s possibly involved in the metabolism of toxic by-products of lignin degradation. Genes encoding enzymes in pathways involved in the production of potentially phytotoxic metabolites are also present.…”
Section: Introductionmentioning
confidence: 99%